Indoor Vertical Farming Systems for Food Security and Resource Sustainability - Jiangxiao Qiu; Haimanote K. Bayabil; Yuncong Li (EDIS)
Indoor vertical farming has been gaining increased popularity worldwide as a method of addressing food security while satisfying sustainability needs. This fact sheet written by and published by the UF/IFAS provides a comprehensive summary of the current status of indoor vertical farming in the United States and globally, commercial derivatives, major sustainability benefits and limitations and challenges. Learn about the limitations and challenges of the industry as well as the potential benefits both for food security and resource sustainability. https://edis.ifas.ufl.edu/fr429